SELEKSI HABITAT LUTUNG JAWA DI TAMAN NASIONAL GUNUNG MERAPI - , QURROTU AYUNIN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research describes the Habitat Selection by the javan langur (Trachypithecus auratus) in the Mount Merapi National Park (MMNP). Javan langur was selected as the object of the research because it plays an important role in ecology. It affects the pattern of forest regeneration and the diversity of tree species in the habitat. Declining tendency of the javan langur population made this research was interesting to be conducted, especially these animals were in a unique ecosystem region of the most active volcanoes on Java Island. The aims of this research were to determine biotic and abiotic components affecting habitat selection by javan langur in MMNP and indentify characteristics of the habitat selected by javan langur at the level homerange and microsite. Chisquare test was applied to determine whether habitat selection is occurred or not. While, logistic regression was applied to predict the variables affecting the probability of the presence of javan langur. Study of habitat selection by javan langur was conducted over three months, from September to November 2012. Chi-square test showed that there were a habitat selection by javan langur in MMNP. Characteristics of the habitat selected by the javan langur at the level of home range such as: on the region with the altitude between 1500-2000 meters asl, more than 45% of slope area, average amount of trees were 139 trees/hectare, average amount of fodder trees were 47 trees/hectare, average of basal area were 9.4 m 2 /hectare and low-interferences of human. These characteristics were found in Block Wonopedut and Block Songgobumi of MMNP. Based on logistic regression analysis, the probability of the presence of javan langur increased with the growing of basal area of the trees, number of fodder trees, altitude and distance from the interference. The probability of the presence of Javan langur dwindle if more and more number of trees and away from the river. The sites characteristics selected by javan langur were on the region with 75-350 trees/hectare, 75-300 fodder trees/hectare, 7,31-54,52 m 2 /hectare of basal area, altitude of 1456-1900 asl, distance from the river between 3-189 m and distance from the interference between 7-448 m.